Orthodoxy, liberalism, and adaptation : essays on ways of worldmaking in times of change from biblical, historical, and systematic perspectives - Becking, Bob. (Studies in Theology and Religion, 2011)
How does religion cope with changing situations? Are orthodoxy and liberalism really competing strategies? The essays in this volume argue three views. (1)Orthodoxy is not to be seen as the real and original form of a given religion, but as an idealized original form that should be construed as a construction in reaction to changes in time. (2) Over the ages, liberalism - despite its laudable strive for adaptation - has been less successful than generally assumed. This lesson from history can be quite important in view of the adaptation processes for Muslims in Western Europe. (3) Of great importance for the survival of religion seems to be a clear definition of the boundaries of religiously informed practices and ethics. Their recognisability and authenticity shall - when combined with a due lack of obtrusion - be of great influence for the ongoing acceptance of religion(s) in the public domain.